Inquiry-Based Learning With Abcde Methods In Early Childhood Education (THUFULA, 2023)
Early childhood has privileges to play. To make them enjoy their learning process, the teacher has to make it more fun for them with play activities. Inquiry-based learning is one of the methods to support children playing while learning. Teachers should make the early childhood curriculum interesting for them. The Purpose of this study is to describe the Inquiry-based Learning with ABCDE Methods in Early Childhood Education. Besides that, the researcher wants to find out how the Inquiry-based Learning keep playing activities in learning process. The researcher collected data through interviews, observations, and documents. The researcher takes interviews with the Principal, The teacher, and the Co-Teacher. This Field Research site is RA Banat Kudus. Qualitative Method was adopted to analyze research data. The result of the Research are (1) The step of implementing the Inquiry-based Learning are observing, asking, telling, discussing and evaluation (ABCDE Methods) (2) With a right play activities, learning is more fun.